CONGENITAL HYDRONEPHROSIS: DISEASE OR CONDITION? - Petrovski M; SImeonov R; Todorovikj L; Chadikovski V; Memeti, Sh; Petrovska B; Risteski T; Cvetanovska V (Macedonian Academy of Sciences and Arts / Sciendo, 2014)
Abstract The aim of this paper is to address the dilemmas of the paediatric surgeon when facing an isolated, unilateral, congenital hydronephrosis and discuss the strategic options for the management of this condition. Congenital hydronephrosis, the most commonly diagnosed uropathy in children, is usually a benign and self-resolving condition. Nonobstructive hydronephrosis does not require operative treatment, while timely treatment is imperative for obstructive hydronephrosis before significant renal damage ensues. Managing congenital hydronephrosis is a challenging task. Thirty-two children with unilateral, isolated hydronephrosis and nonobstructed renography curves were followed up for 3 years. On the initial evaluation according to the grade of hydronephrosis: 22.6% were grade I, 54.8% grade II and 22.6% grade III. After 12 months of follow-up: 30% were grade I, 51.5% grade II and 18.5% grade III, respectively. After the three-year follow-up, there were no hydroneproses greater than grade II. The mean value of the separate GFR of the affected kidney at initial evaluation was 42.83%, and 40.33% after three years. In three children the treatment was converted from conservative to surgical. Nonobstructive, congenital hydronephrosis is a benign condition not requiring any medical treatment, but aggressive observation is indicated.
Keywords: congenital hydronephrosis; management; child